Leptospira spp. of the Urinary Tract of Female Carrier Goats in Semi-Arid Conditions - Rocha, Laysa Mayara Soares Brito; Faria, Pedro Jorge Alvares de; Soares, Rafael Rodrigues; Araujo Junior, Joao Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Silva, Maria Luana Cristiny Rodrigues; Higino, Severino Silvano dos Santos; Azevedo, Sergio Santos de; Alves, Clebert Jose (Univ Fed Rio Grande Do Sul, 2022)
Background: Leptospirosis is an important infectious disease in goat farming, with a worldwide distribution. It is usually transmitted by rodents and the genital route, may cause reproductive losses, negatively impacting goat fanning. The diagnosis lies on serological, molecular and isolation techniques. Considering the importance of this disease for small ruminants, this work aimed to evaluate the serological, molecular findings and isolation of pathogenic leptospires in the urinary tract (kidney and bladder tissues) of goats. Materials, Methods & Results: Thirty-four adult goats were used for slaughter. Renal samples (n = 34), bladder (n = 34), were collected for isolation of the agent and molecular detection of Leptospira sp. and blood samples (n = 34) for serological testing. The polymerase chain reaction (PCR) was used as a molecular test and the microscopic serum agglutination test (MAT) was used as a serological test. Samples with DNA amplification were subjected to genetic sequencing. The presence of Leptospira DNA was found in the tissues of 8 (23.4%) goats, and of these, only 2 were positive in PCR and MAL There was a slight agreement between the PCR and MAT techniques (k = 0.150; P = 0.436). In 6 (17.6%) samples of renal tissue and 2 (5.8%) bladder samples, Leptospira DNA was detected. The genes in a kidney tissue sample were sequenced and demonstrated 99% similarity to Leptospira interrogans. Anti-Leptospira sp. were detected in 6 (17.6%) of the animals tested. Discussion: Serology identified 3 predominant serogroups: Icterohaemorrhagiae, Tarassovi and Autumnalis, serogroups that are related to the presence of rodents that coexist in rural environments. Autumnalis has been reported in small ruminants, raising the hypothesis that goats are adapted, becoming chronic carriers and possible maintenance hosts. The frequency obtained (17.6%) may be the result of the mixed breed pattern and rustic characteristics inherent to the goat species. Given the characteristics of the semi-arid region, such as low rainfall and high solar incidence, it is essential to use an adapted methodology, with a lower cut-off point (1:50), as the serological titer is an established relationship between the animal species, the level of exposure throughout its evolution and the region studied. Molecular findings and bacterial isolation reveal the agent's ability to colonize the urinary tract of goats. These data show the importance that urine has in the epidemiological chain, being able to transmit the agent through direct contact with this product or through contamination of soil and water. There was no statistical agreement between the diagnostic techniques used in this study, in this case, an association between PCR and MAT is recommended to obtain data with high sensitivity and specificity. A bladder sample was sequenced and showed 99% similarity to Leptospira interrogans. In the semiarid region, the most common form of leptospirosis spread is through the sale of animals in business fairs for breeding, rearing or slaughter, as well as sharing the same property with several breeders. The introduction of chronic and asymptomatic carriers on the properties represents a serious risk for the spread of the disease. The results show the presence of Leptospira spp. in semi-arid goat herds, having as risk factors the presence of rodents and intercropping. The association of MAT and PCR is necessary for a better diagnosis of the disease.
Keywords: Leptospirosis; Leptospires; Zoonosis; Serology; Molecular detection; Epidemiology; semiarid